THE REFLECTIONS OF INDONESIAN NATIONAL CHARACTER AND CULTURAL EDUCATION IN GREAT EXPECTATION - Tjitra Ramadhani; Yuliarsih Yuliarsih (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: The expression of life through language is often called literature. Values, customs, cultures, and principles people uphold in the society also constitute the main ingredients for the author to make their own literary works. The researcher wants to build positive characters to her students through this novel. This study is intended to achieve the purpose, is to describe the reflections of Indonesian National Character and Cultural Education through Great Expectations novel. This study is design to obtain information concerning the current status of the phenomena and it exists at the time of the study. The data source of the study is the novel entitled Great Expectations written by Charles Dickens. Also, there are eight reflections of the Indonesian National Character and Cultural Education; those are Religious, Honest, Independence, Curious, Sportive and Respectful, Inclusive and Communicative, Caring and Compassion, and Empathetic. The researcher hopes that the study is able to become meaningful source for the student and the English teacher who wants to conduct the study in literary work. Keywords: novel, character building, Indonesian national character and cultural education.